Fibroblast as a critical stromal cell type determining prognosis in prostate cancer. Issue 13 (3rd July 2019) - Blom, Sami; Erickson, Andrew; Östman, Arne; Rannikko, Antti; Mirtti, Tuomas; Kallioniemi, Olli; Pellinen, Teijo
Abstract: Background: Tumor stroma associates with prostate cancer (PCa) progression, but its specific cellular composition and association to patient survival outcome have not been characterized. Methods: We analyzed stromal composition in human PCa using multiplex immunohistochemistry and quantitative, high‐resolution image analysis in two retrospective, formalin‐fixed paraffin embedded observational clinical cohorts (Cohort I, n = 117; Cohort II, n = 340) using PCa‐specific mortality as outcome measurement. Results: A high proportion of fibroblasts associated with aggressive disease and castration‐resistant prostate cancer (CRPC). In a multivariate analysis, increase in fibroblast proportion predicted poor cancer‐specific outcome independently in the two clinical cohorts studied. Conclusions: Fibroblasts were the most important cell type in determining prognosis in PCa and associated with CRPC. Thus, the stromal composition could be critically important in developing diagnostic and therapeutic approaches to aggressive prostate cancer.